The Goosander and Red-breasted Merganser in Scotland - Mills, Derek (Wildfowl, 1962)
The spread of the Goosander and the Red-breasted Merganser in Scotland is reviewed and their present breeding distribution is described. The Goosander occurs on the upper reaches and small tributaries of rivers, while the Red-breasted Merganser occurs mainly on sea lochs and firths and on the lower reaches of rivers, except in the case of the larger river systems, where it occurs far inland. During the autumn, winter and early spring the Goosander is found on the lower reaches of rivers and on lochs and reservoirs, while the Red-breasted Merganser occurs in very large flocks in the firths and estuaries. The population density of Goosanders on some northern Scottish rivers in summer is of the order of two to three birds per ten miles. The feeding methods of the two species are described. Their enemies are noted, man being much the most important. Reasons for the Goosander becoming a breeding species in this country after 1870 are briefly discussed. The present methods of control have caused little change in their distribution. A study of the birds’ feeding behaviour and migrations would be of great value in assessing their importance as salmon predators.